Enterprise applications, markets and services in the finance industry : 8th International Workshop, FinanceCom 2016, Frankfurt, Germany, December 8, 2016, Revised Papers /: 8th International Workshop, FinanceCom 2016, Frankfurt, Germany, December 8, 2016, Revised Papers. (2017) - Unknown
No abstract available